2023
DOI: 10.1007/s12011-023-03587-2
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Oxide Nanoparticles and Vitamin C Ameliorate Atrazine-Induced Hepatic Apoptosis in Rat via CYP450s/ROS Pathway and Immunomodulation

Abstract: Atrazine, as an herbicide, is used widely worldwide. Because of its prolonged persistence in the environment and accumulation in the body, atrazine exposure is a potential threat to human health. The present study evaluated the possible protective effects of zinc oxide nanoparticles and vitamin C against atrazine-induced hepatotoxicity in rats. Atrazine administered to rats orally at a dose of 300 mg/kg for 21 days caused liver oxidative stress as it increased malondialdehyde (MDA) formation and decreased redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Therefore, it is only at experimental doses, and not at relevant environmental concentrations has ATZ-induced hepatotoxicity been established for mammalian animals. However, one study (Jestadi et al, 2014), have demonstrated hepatotoxicity associated with elevated serum aspartate aminotransferase and alanine aminotransferase activity in animals exposed to ATZ at doses of 300 μg/kg b.w, which is more than 1,000 times lower than was used in the above studies (Campos-Pereira et al, 2012;Mohammed et al, 2023;Rashad et al, 2023). Thus, the proposal that ATZ effects, in mammalian animals may be influenced by differences in methodologies, sources and purity of chemical, solvents, and statistical analyses (Kligerman et al, 2000b), are important concepts to consider in studies focusing on ATZ-induced liver injury in animal models.…”
Section: Chemopreventive Intervention With Selected Antioxidantsmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, it is only at experimental doses, and not at relevant environmental concentrations has ATZ-induced hepatotoxicity been established for mammalian animals. However, one study (Jestadi et al, 2014), have demonstrated hepatotoxicity associated with elevated serum aspartate aminotransferase and alanine aminotransferase activity in animals exposed to ATZ at doses of 300 μg/kg b.w, which is more than 1,000 times lower than was used in the above studies (Campos-Pereira et al, 2012;Mohammed et al, 2023;Rashad et al, 2023). Thus, the proposal that ATZ effects, in mammalian animals may be influenced by differences in methodologies, sources and purity of chemical, solvents, and statistical analyses (Kligerman et al, 2000b), are important concepts to consider in studies focusing on ATZ-induced liver injury in animal models.…”
Section: Chemopreventive Intervention With Selected Antioxidantsmentioning
confidence: 96%
“…These biochemical alterations were found to induce inflammation associated with apoptosis through up-regulating Bax, nuclear factor-kappa B, TNF-α and minimising Bcl-2 gene expressions in the hepatic tissues. Light microscopy of liver sections was typified with vacuolated and degenerated hepatocytes surrounding dilated and congested blood sinusoids and central veins ( Mohammed et al, 2023 ). Additionally, the serum samples obtained from the animals were characterised with higher level of aspartate aminotransferase and alanine aminotransferase enzyme activity, and diminished albumin and globulins concentrations confirming liver toxicity.…”
Section: Chemopreventive Intervention With Selected Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation